Strength matters: correlation of maximum strength, jump, and sprint performance with on-ice sprint performance across age and skill levels in ice hockey - Gerg, A.; Wagner, C. M.; Keiner, M. (Sport Sciences for Health, 2024)
Maximum strength has a significant impact on sprint or jump performance, which is a major physical key performance indicator in ice hockey. The study aimed to assess the correlation between off-ice maximum strength and vertical jump performance with on-ice linear sprint performance, while considering age and performance level. A total of 72 male national- and international-level (Tier 4) youth and adult professional ice hockey players were recruited for the study. The participants were divided into four age groups: under 13, 15, 17 years old, and professional players (i.e., >18 years). Jump performances (squat jump, countermovement jump, standing long jump), maximum strength (one-repetition maximum in squat), off-ice and on-ice linear sprints (20-m with split times at 10 m) were measured. Statistical analysis revealed that maximal strength has a moderate to strong correlation with on-ice linear sprint performance (r = -0.37 to -0.51), without any influence of age group or performance level. The study also found significant differences in maximal strength and jumping performance (d = 0.20-6.15), as well as both on- and off-ice linear sprints (d = 0.56-6.15), with older age categories outperforming younger ones across different age groups and performance levels. The effect sizes observed were notably high, suggesting a substantial impact that may be attributed to both selection and training processes. The study shows that maximum strength significantly affects on-ice sprint performance in ice hockey players. To improve the transition from youth to elite level, it is recommended to train these variables, as almost all maximum strength and sprint as well as jump performances (on- and off-ice) show differences from youth teams to professionals.